Kinerja Layanan Publik Dinas Informasi dan Komunikasi Kota Makassar - Annas, Aswar; M, Nursafitra; P, Resky Amalia (Jurnal Publisitas, 2022)
The performance of government administrators significantly affects public services and the success of a government if the quality of services provided is considered reasonable by the service recipients (the community). The purpose of this study is to determine the condition of public service performance at the Makassar City Information and Communication Service. The research method used is descriptive qualitative by involving the community and employees as informants. The study's results suggest that service productivity that occurs when employees provide public services is considered very responsive. Employees have shown a form of service that is fast, precise, and full of discipline. However, it is still necessary to provide Standard Operating Procedures (SOPs) to support more effective services. So far, the quality of service has been assessed by employees as showing politeness, friendliness, smiles, and free service. Employees are pretty respectful in providing services to users of public services. The responsiveness of employees is considered maximal, and the capacity of employees is quite capable of explaining the administrative requirements that are equipped to obtain benefits. However, the overall service's increase in HR/operator capacity needs to be improved. Service responsiveness is considered quite good. Employees care enough to provide services but still need to be equipped with several service instruments in each service unit, such as Standard Operating Procedures (SOP). So far, service accountability is considered by employees to be entirely responsible for providing a service. Some employees can understand and explain the flow and mechanism for obtaining assistance to service users.